Gastric volvulus: a case report - Emilio Guerra Pérez; Marcial Llamas Fonte; Lidia Torres Aja (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Gastric volvulus is a rare entity that was first described by Berti in 1866 while performing a necropsy. In 1896, Berg first established the diagnosis during the operation. In 1904, Borchardt described the classic triad of epigastric distension with pain, difficulty for the nasogastric tube to pass and nausea without vomiting. A case of a female patient aged 73 and 56 kg in weight, with a history of ischemic heart disease and gastric ulcer, who visited the emergency department because of vomiting, diffuse abdominal pain and bloating is presented. She had a surgery on an urgent basis to confirm the diagnosis of mixed gastric volvulus without vascular compromise. Gastropexy was performed with the diaphragm. This patient progressed satisfactorily, allowing hospital discharge 72 hours after surgery. Due to the weirdness of this case it was decided to have it published.